Meal Pattern of Malnutrition Children Under 5 Years and Related Factors - Sophia, Fanjaniaina; Suherni, Suherni; Kuswardinah, Asih (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Malnutrition prevalence in Indonesia has increased from 2007 to 2013. Research was conducted on Kabupaten Brebes which rank 29 of 35 Kabupaten/City on Jawa Tengah province in malnutrition case and meal pattern is found as related factor. The research objective is to obtain malnutrition children under 5 years Â meal pattern and others related factors. Reseach was conducted in 2016 by quantitative approach and supported with qualitative datas. Sampling method by total sampling from 32 mother and children under 5 years with malnutrition status. Research instrument consist of questionnaire and food recall instrument accompanied with observation guide. The quantitative datas are analysed by descriptive method and chi square statistic test. Result shown most of malnutrition children under 5 years meal pattern is improper (75%) and children under 5 years feeding is not proper to itâ€™s nutrition requirement. Whether the nutrition, quantity and frequention of the feeding. This is relation between level of knowledge, education, family income with meal pattern (p value < 0.005) and no relation between numbers of family member with meal factor of malnutrition children under 5 years (p value = 1.00) at work region of Puskesmas Brebes. Respondent does not know proper food for children under 5 years, proper food for each children under 5 years age yet aware that the food must be cooked to produce soft texture.